2022
DOI: 10.1186/s12877-022-02937-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher hemoglobin levels are associated with better physical performance among older adults without anemia: a longitudinal analysis

Abstract: Background Anemia is the most common hematological abnormality among older adults, and it is associated with decreased physical performance. But the role of hemoglobin in the absence of anemia remains unclear. Thus, this study aimed to assess the impact of hemoglobin levels on physical performance in Brazilian older adults without anemia. Methods The study is longitudinal in that it relies on two waves of the Saúde, Bem-Estar e Envelhecimento (SABE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The gender comparison-by using all three cut-off levels-in non-anemic subjects showed that men had a better cognitiveaffective, functional, and nutritional status than women. As expected [45,46], from our data, it emerged that anemic patients showed a more advanced age, a greater deflection of mood, less functional capacities, malnutrition, and more severe comorbidities. On the contrary, however, we did not observe a greater cognitive impairment in anemic patients, in agreement to some evidence [47].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The gender comparison-by using all three cut-off levels-in non-anemic subjects showed that men had a better cognitiveaffective, functional, and nutritional status than women. As expected [45,46], from our data, it emerged that anemic patients showed a more advanced age, a greater deflection of mood, less functional capacities, malnutrition, and more severe comorbidities. On the contrary, however, we did not observe a greater cognitive impairment in anemic patients, in agreement to some evidence [47].…”
Section: Discussionsupporting
confidence: 83%
“…The causes of anemia in the elderly are various and often more than one contributes to its genesis. Anemia has been associated with increased comorbidity (including neurological and psychiatric disorders), worsening physical performance, quality of life, and increased frequency and duration of hospital admissions [45][46][47][48][49][50]. Despite its clinical importance, anemia in the elderly is poorly recognized and the evidence-based guidelines for its management are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia decreases a patient's oxygen-carrying capacity, weakens muscle strength, and decreases body activity and physical state (34). The findings of the present study indicated that at the end of 3 months of treatment, hemoglobin in HCF group was significantly higher than that of the control group.…”
Section: Discussionmentioning
confidence: 43%
“…Hemoglobin level not only reflected the nutritional status but also was an indicator for the complications and outcomes 13 15 . A longitudinal analysis in old adults without anemia showed that higher hemoglobin levels were linked with better physical performance 16 . One observational study found that in patients with hip fracture, preoperative hemoglobin levels ≥ 10 g/dl lead to a 50% decreased risk of mortality compared to patients with hemoglobin levels < 10 g/dl (hazard ration(HR) = 0.50, 95% CI 0.25–0.99, P = 0.048) 17 .…”
Section: Discussionmentioning
confidence: 99%